Pengaruh Model Discovery Learning terhadap Kemampuan Pemecahan Masalah Matematis Siswa: Meta Analisis - Sashi Kirana Zahrani Putri; Hasanuddin Hasanuddin (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
Discovery Learning (DL) is increasingly being applied in mathematics learning, but in-depth studies are still needed to assess the extent to which this method is effective in improving students' abilities in solving mathematical problems, as well as analyzing various existing research regarding the impact of DL models on students' problem-solving abilities. This research aims to analyze various existing research results regarding the influence of DL models on students' problem-solving abilities. This study is very important to provide strong evidence about the effectiveness of DL, so that it can help educators make evidence-based decisions in the mathematics learning process. For its methodology, this research uses quantitative meta-analysis by conducting a systematic review of 12 research articles published between 2017 and 2024, and calculating the effect size. The results of the meta-analysis show that the DL model has a significant influence on mathematical problem solving abilities (KPMM), with an effect size reaching 2.569, which shows a large impact in improving this competency. This research contributes to strengthening empirical evidence regarding the effectiveness of DL in mathematics education, especially in terms of developing problem-solving abilities. These findings suggest that educators should consider integrating the DL model in mathematics teaching to improve students' problem-solving abilities.